PENGARUH OPERATING CAPACITY, SALES GROWTH, DAN CASH FLOW TERHADAP FINANCIAL DISTRESS - Tinambunan, Ave Lamria; Ave Lamria Tinambunan (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This study aims to determine the effect of Operating Capacity, Sales Growth, and Cash Flow simultaneously affect Financial Distress. The object of this research is a Property and Real Estate Company listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The research method used is a quantitative method with sample selection using purposive sampling. The population used in this study is Property and Real Estate Companies listed on the IDX per 2018-2022 which amounted to 62 companies. The total sample in this study became 11 out of 62 companies that met the sample selection criteria. The data used are secondary data obtained from IDX, the Indonesia Stock Exchange website and the company's official website in the form of an annual report using the panel data regression analysis method. The data studied will be processed using Eviews version 12. Based on the tested results show that Operating Capacity, Sales Growth, and Cash Flow simultaneously affects Financial Distress. Keywords : Operating Capacity, Sales Growth, Cash Flow, and Financial Distress